2022
DOI: 10.1016/j.ijso.2022.100508
|View full text |Cite
|
Sign up to set email alerts
|

Local wound infiltration with a mixture of tramadol and bupivacaine versus bupivacaine alone in those undergoing lower abdominal surgery: Prospective cohort study, 2020

Abstract: Background: Postoperative pain can have immediate and long-term consequences, including poor outcomes and prolonged hospitalization. It can also lead to chronic pain if not treated. Wound site infiltration with local anesthetic agents provides desirable analgesia for postoperative pain relief. The purpose of this study was to compare the analgesic effectiveness of local wound infiltration with a mixture of bupivacaine and tramadol (BT) versus bupivacaine alone (BA) for postoperative analgesia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The estimated postoperative pain-free period was comparable (P = 0.01) for the two groups. The rst rescue periods for both groups and the total amount of rescue analgesic required were comparable (P > 0.05) (31). The discrepancies may be due to the difference in the study population, sample size, and drug dosage used.…”
Section: Discussionmentioning
confidence: 88%
“…The estimated postoperative pain-free period was comparable (P = 0.01) for the two groups. The rst rescue periods for both groups and the total amount of rescue analgesic required were comparable (P > 0.05) (31). The discrepancies may be due to the difference in the study population, sample size, and drug dosage used.…”
Section: Discussionmentioning
confidence: 88%
“…It was reported that the addition of 100 mg tramadol to 0.25% bupivacaine fastens the onset and prolongs the duration, compared with 0.25% bupivacaine given alone ( 38 ). Similarly, local wound infiltration of bupivacaine-plus-tramadol was more effective than bupivacaine alone in decreasing postoperative pain during lower abdominal surgery ( 39 ). In dentistry, the local anesthetic efficacy of tramadol has been mainly evaluated during oral surgical procedures.…”
Section: Discussionmentioning
confidence: 99%